Source, temporal variation and health risk of volatile organic compounds (VOCs) from urban traffic in harbin, China. (1st February 2021) - Xuan, Lichun; Ma, Yuenan; Xing, Yanfeng; Meng, Qingqing; Song, Jie; Chen, Taihan; Wang, Hao; Wang, Pengjie; Zhang, Yufan; Gao, Peng
Abstract: The main of this work investigated the levels, emission sources, and associated health risks of ambient volatile organic compounds (VOCs) closed urban traffic trunk from June 2017 to November 2018. The seasonal variation trend for total VOCs (TVOCs) concentrations was autumn > winter > summer > spring. During the daily fluctuations in summer, the TVOC concentrations appeared to be the highest at midnight and the lowest at 14:00. In spring, autumn, and winter, the concentrations of TVOCs reached the highest levels at 06:00 and dropped to the lowest levels at 14:00 to 15:00; then, the levels increased after 20:00. Aromatics were the most important types of ambient VOCs for the formation of secondary organic aerosols (SOAs). The Positive Matrix Factorization (PMF) source analysis indicated that the traffic emission accounted for 28.9% of TVOCs, followed by combustion (24.7%), industrial (21.3%), gasoline volatilization (12.4%), and solvent (11.7%) sources. Carcinogenic and non-carcinogenic risks via inhalation exposure to the selected 10 toxic VOCs may be of more concern for residents nearby traffic trunk in Harbin in autumn. Graphical abstract: Image 1 Highlights: Temporal variations in VOCs were studied over two years from a closed urban traffic. Alkanes were the dominant compounds detected during entire observation period. VOCs peaked at midnight in summer and in the early morning hours in other seasons. Seasonally, TVOC concentrations were ranked as autumn > winter > summer > spring. Abstract : Characteristics of VOCs distribution and exposure at near traffic environment in congestion city.